Determinants of Consumers’ Adoption of Mobile Parking Payment Services in Kenya - Komo, Lee; Kyando, Eusebius; Ngare, Philip (Sabinet, 2016)
We conduct a study on consumers‟ satisfaction and acceptance of mobile parking service: EJIJIPAY, in Nairobi City-Kenya. We begin by assessing consumers‟ satisfaction of EJIJIPAY since its launch. We perform factor and cluster analysis on a sample data collected amongst mobile parking payment users in Nairobi. The analysis gave evidence that EJIJIPAY provides advantages on reliability, cost savings and access. We then determine what actions consumers are likely to take after using the service, determine usage habits and acceptance of the service. Our results shows that the new mobile parking payment innovation has not only improved county returns but also led to higher levels of consumers‟ satisfaction. We therefore conclude that EJIJIPAY service is an important parking solution for Nairobi City. The service curbs corruption, maximizes parking revenues and is an efficient payment system. We also survey trends of the mobile parking payment technologies in other cities and best implementation strategies that will help enhance their usage.
Keywords: EJIJIPAY; Mobile parking financial service; Customer behavior; Factor analysis; Cluster analysis.